Kausalitas Penanaman Modal Dalam Negeri, Penanaman Modal Asing dan Penyerapan Tenaga Kerja di Indonesia - Mutia Ferina; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aims to determine and analyze the causality of Domestic Investment (PMDN), Foreign Investment (PMA), and Labor Absorption in Indonesia. This type of research is descriptive and associative research that is research that describes the research variables and find the presence or absence of causality between each of these variables. The type of data in this study are secondary data and panel data from 2013-2017 per Province in Indonesia. Analysis of the data used is descriptive analysis and inductive analysis. In inductive analysis there are several tests, namely: Analysis of Vector Auto Regression (VAR), Empirical Model Analysis of Vector Auto Regression (VAR), Steps of Analysis of Vector Auto Regression (VAR) such as: Root Unit Test (Panel Root Test), Coordination Test ( Panel Cointegration Test), Optimum Lag, Granger Causality Test, Stability Test, Implementation of Vector Auto Regression (VAR) Models. The results of this study indicate that (1) domestic investment and foreign investment are not qualified in Indonesia, (2) foreign investment and absorption of unsuspected workers in Indonesia, (3) domestic investment and absorption of qualified workers in Indonesia.